1994
DOI: 10.1007/bf00023237
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of an Arabidopsis oleosin gene promoter in transgenic Brassica napus

Abstract: Progressive deletions of the 5'-flanking sequences of an Arabidopsis oleosin gene were fused to beta-glucuronidase (GUS) and introduced into Brassica napus plants using Agrobacterium-mediated transformation. The effect of these deletions on the quantitative level of gene expression, organ specificity and developmental regulation was assessed. In addition, the influence of abscisic acid (ABA), jasmonic acid (JA), sorbitol and a combined ABA/sorbitol treatment on gene expression was investigated. Sequences that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…In Figure 7, it can be seen that wild-type B. carinata produced no detectable signals, whereas B. napus GB5 plants (oleosin promoter-GUS; Plant et al, 1994) gave a strong reaction to GUS antibodies at the expected size of free GUS (68 kD). OBPGUSA generated the expected full-length product at 86 kD.…”
Section: Proline Knot Motif Is Critical In Vivo For Oil Body Targetinmentioning
confidence: 99%
“…In Figure 7, it can be seen that wild-type B. carinata produced no detectable signals, whereas B. napus GB5 plants (oleosin promoter-GUS; Plant et al, 1994) gave a strong reaction to GUS antibodies at the expected size of free GUS (68 kD). OBPGUSA generated the expected full-length product at 86 kD.…”
Section: Proline Knot Motif Is Critical In Vivo For Oil Body Targetinmentioning
confidence: 99%
“…Using an oleosin promoter from protein thioesterase from seeds of the California Bay {Umbel-Arabidopsis fused to the gus gene. Plant et al (1994) performed lularia californica) resulting in plants accumulating up to 50% truncation-and activation analysis of oilseed rape. The GUS lauric acid (Voelker et al 1992).…”
Section: Assessment Of Transgenic Plantsmentioning
confidence: 99%
“…Applying an oleosin gene promoter from Arabidopsis, the ^-glucoronidase gene product was targeted to the oleosomes of Brassica napus (Plant et al 1994). This property can be exploited for the production and partial purification of recombinant proteins or directly applied as oilbody-immobilized enzymes in industrial processes (van Rooijen and Moloney 1995).…”
Section: Other Traitsmentioning
confidence: 99%
“…Abscisic acid (ABA) also plays an important role in expression of seed-storage protein genes and embryogenesis related genes (Luo et al, 2008). Plant et al (1994) showed that ABA positively regulated expression of GUS in transgenic Brassica containing the oleosin promoter from Arabidopsis fused to the reporter gene. Rowley and Herman (Rowley and Herman, 1997) found that soybean oleosin genes contain regulatory elements in the upstream region which also were found in vacuolar storage protein genes.…”
Section: Discussionmentioning
confidence: 99%